2016
DOI: 10.3389/fnmol.2016.00135
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Minocycline Against Ketamine-Induced Injury in Neural Stem Cell: Involvement of PI3K/Akt and Gsk-3 Beta Pathway

Abstract: It has been suggested that ketamine cause injury during developing brain. Minocycline (MC) could prevent neuronal cell death through the activation of cell survival signals and the inhibition of apoptotic signals in models of neurodegenerative diseases. Here we investigated the protective effect of MC against ketamine-induced injury in neural stem cells (NSCs) from neonatal rat. Ketamine (100 μM/L) significantly inhibited NSC proliferation, promoted their differentiation into astrocytes and suppressed neuronal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 40 publications
(51 reference statements)
2
13
0
Order By: Relevance
“…Interestingly, we found that minocycline alleviates cellular proliferating changes induced by midazolam in neurogenetic regions of neonatal rats, indicating that minocycline might enhance NSC proliferation following midazolam exposure during the brain development which is benefit for the neurogenesis. The finding about the neuroprotection of minocycline on brain development is in consistency with our recent study, which reported the protective effect of minocycline against ketamine-induced injury in NSCs 17 . Whether minocycline can mitigate midazolam-induced neuroapoptosis needs to be determined further.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, we found that minocycline alleviates cellular proliferating changes induced by midazolam in neurogenetic regions of neonatal rats, indicating that minocycline might enhance NSC proliferation following midazolam exposure during the brain development which is benefit for the neurogenesis. The finding about the neuroprotection of minocycline on brain development is in consistency with our recent study, which reported the protective effect of minocycline against ketamine-induced injury in NSCs 17 . Whether minocycline can mitigate midazolam-induced neuroapoptosis needs to be determined further.…”
Section: Discussionsupporting
confidence: 92%
“…The positive outcome of minocycline is associated with inhibition of microglia activation 14 , inhibition of caspase-1 and caspase-3 15 , and cytochrome c release 16 . Recently, we reported that minocycline attenuated ketamine-induced injury in neural stem cells (NSCs) 17 and restores neurogenesis in the subventricular zone (SVZ) and the subgranular zone (SGZ) of the hippocampus after ketamine exposure in neonatal rats 18 . However, whether minocycline can attenuate the developmental neurotoxicity of midazolam remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro , Res up-regulated the expression of p-Akt and p-p300, which were co-localized in the PC-12 cells ( p < 0.01 ). LY294002, an inhibitor of Akt signaling (Lu et al, 2016 ), down-regulated the expression of p-p300 ( p < 0.05 , Figures 3D–F ), suggesting that the Res-induced phosphorylation of p300 was mediated via Akt signaling. In addition, these results may indicate that Res enhanced the activity of p300 acetyltransferase, as the phosphorylation of p300 at Ser-1834 is believed to be essential for this activity (Huang and Chen, 2005 ; Liu et al, 2006 ; Chen et al, 2015 ).…”
Section: Resultsmentioning
confidence: 90%
“…Lu et al [18]aimed to elucidate a possible mechanism underlying the neuroprotective effect of minocycline by using LY294002 to inhibit the PI3K pathway. Immunoblotting revealed that minocycline enhanced phosphorylation/activation of Akt and phosphorylation/inactivation of GSK3β.…”
Section: Discussionmentioning
confidence: 99%